“The Good into the Pot, the Bad into the Crop!”—A New Technology to Free Stem Cells from Feeder Cells - Schneider, Annette (Public Library of Science, 2008)
A variety of embryonic and adult stem cell lines require an intial co-culturing with feeder cells for non-differentiated growth, self renewal and maintenance of pluripotency. However for many downstream ES cell applications the feeder cells have to be considered contaminations that might interfere not just with the analysis of experimental data but also with clinical application and tissue engineering approaches. Here we introduce a novel technique that allows for the selection of pure feeder-freed stem cells, following stem cell proliferation on feeder cell layers. Complete and reproducible separation of feeder and embryonic stem cells was accomplished by adaptation of an automated cell selection system that resulted in the aspiration of distinct cell colonies or fraction of colonies according to predefined physical parameters. Analyzing neuronal differentiation we demonstrated feeder-freed stem cells to exhibit differentiation potentials comparable to embryonic stem cells differentiated under standard conditions. However, embryoid body growth as well as differentiation of stem cells into cardiomyocytes was significantly enhanced in feeder-freed cells, indicating a feeder cell dependent modulation of lineage differentiation during early embryoid body development. These findings underline the necessity to separate stem and feeder cells before the initiation of in vitro differentiation. The complete separation of stem and feeder cells by this new technology results in pure stem cell populations for translational approaches. Furthermore, a more detailed analysis of the effect of feeder cells on stem cell differentiation is now possible, that might facilitate the identification and development of new optimized human or genetically modified feeder cell lines.